PENGARUH PENAMBAHAN GULA PASIR TERHADAP UMUR RENCANA BETON (The Effect Of Addition Of Sugar On The Design Of Concrete) - Yanshon Happy; Brian Naldo Giovanni (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2021)
Retarder is an auxiliary chemical to slow down the initial setting time so that the mixture remains workable for a longer time. In general, sugar-containing raw materials can be used as retarder or water reducer sets. Granulated sugar is a material that is widely available and is expected to fulfill this. This research aims to determine the effect of sugar on concrete bonding time and the effect on concrete compressive strength. In this activity, preparations were made for the manufacture of test specimens, from preparing tools and materials such as cement, coarse aggregate, fine aggregate, water, and sugar, as well as a survey to the Laboratory to check the tools to be used for making test specimens. Testing will be carried out for 21 days, 28 days and 35 days. After all the data is obtained, data processing will be carried out to obtain research results. K-125 concrete is included in the class II category which can be used for structural works in general. From the results of this study it is known that the initial setting time is 2 hours for normal concrete (BN) and 5 hours for concrete with mixed solution. sugar (BG30). From the results of the cement setting time test it proves that the sugar solution makes the cement setting time longer (Initial Setting Time). Keywords: Concrete, Compressive Strength, Time, Age of Concrete, Test Objects